Implementation of Fulfilling The Constitutional Rights of Citizens in Religion: Case Study of Batur Village, Indonesia - Cholida Hanum (Faculty of Law, Universitas Pekalongan, 2025)
In recent years, various events showing the existence of religious freedom have become a phenomenon. Violation of respect for the individual’s freedom to embrace and practice religious freedom has an impact on all aspects of life, including education, health, employment, and access to public services. As the national organizer, the government plays an important role in creating a favorable, safe and peaceful atmosphere for the people. The slogan of Bhinneka Tunggal Ika seems to be only utopian, which is reflected in the civil relations in the village of Batur, where occupations are multi-religious. But it is important to note that the term